Trends and Challenges for Quality of Service and Quality of Experience for Wireless Mesh Networks - Aguiar, Elisangela S.; Pinheiro, Billy A.; Figueirêdo, João Fabrício S.; Cerqueira, Eduardo; Abelém, Antônio Jorge. G.; Gomes, Rafael Lopes (IntechOpen, 2011)
None